A positive electrode material and its preparation method and application

The positive electrode material of sodium ion battery is coated by Ba2FeVxMo1-xO6 and YSZ, which solves the problem of insufficient stability and electrochemical performance of the positive electrode material in high temperature environments, and achieves excellent cycling performance and stability under high temperature conditions.

CN118983428BActive Publication Date: 2025-03-07ZHUJI PAWA NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411474552.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-03-07
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The stability and electrochemical performance of sodium ion battery positive electrode materials in high temperature environments lead to a shortened battery cycle life and a decrease in electrochemical performance.

Method used

Ba2FeVxMo1-xO6 and YSZ (yttrium-stable zirconium oxide) were used to coat the matrix material to improve the conductivity and structural stability of the positive electrode material, and to inhibit the decomposition reaction between the electrolyte and the positive electrode material.

Benefits of technology

It significantly improves the stability and conductivity of the positive electrode material under high temperature environment, extends the cycle life of the battery, improves the electrochemical performance, and enables the battery to have excellent cycle performance and stability under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118983428B_ABST
    Figure CN118983428B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of sodium ion battery materials, and discloses a positive electrode material, comprising a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on at least a portion of the surface of the substrate, and the second coating layer is coated on at least a portion of the surface of particles formed by the first coating layer and the substrate; the substrate is NaNi x1 Fe y1 Mn z1 O2, x1≤0.8, y1≤0.4, z1≤0.4, x1+y1+z1=1; the first coating layer is Ba2FeV x Mo 1‑x O6, 0.01≤x≤0.1; the second coating layer is YSZ (yttrium stabilized zirconia). x Mo 1‑x O6 and YSZ are used to coat the base material to improve the cycle performance, stability and conductivity of the positive electrode material. In addition, the present invention also discloses a method for preparing the positive electrode material, which is used to prepare the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field related to sodium ion battery materials, and relates to a sodium ion battery positive electrode material, and specifically to a positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles, electronic equipment and energy storage, the demand for lithium-ion batteries has increased rapidly year by year. Coupled with the shortage of lithium resources, the supply and demand of lithium is unbalanced, thus restricting the development of the battery industry. The electrochemical behaviors (migration mechanism, reversible ion storage, etc.) of sodium-ion batteries and lithium-ion batteries are extremely similar, and the sodium element is abundant in the earth's crust and in seawater, and the price is low, which makes sodium-ion batteries replace lithium-ion batteries to enter the market.

[0003] In the prior art, the performance of sodium-ion batteries, especially their stability under extreme conditions such as high temperature, is poor. In particular, the positive electrode materials of sodium-ion batteries are prone to phase change or interface failure at high temperatures, which affects the stability and electrochemical properties of the positive electrode materials, resulting in a shortened cycle life of the battery and a decrease in electrochemical performance, affecting the development prospects of sodium-ion batteries. Summary of the invention

[0004] In view of the defects and shortcomings of the prior art, in the first aspect, the present invention provides a positive electrode material. In the second aspect, the present invention provides a method for preparing the positive electrode material. In the third aspect, the present invention provides a battery.

[0005] In a first aspect, the present invention provides a positive electrode material, comprising a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on at least a portion of the surface of the substrate, and the second coating layer is coated on at least a portion of the surface of particles formed by the first coating layer and the substrate; the substrate is NaNi x1 Fe y1 Mn z1 O2, 0<x1≤0.8, 0<y1≤0.4, 0<z1≤0.4, x1+y1+z1=1; the first coating layer is Ba2FeV x Mo 1-x O6, 0.01≤x≤0.1; the second coating layer is YSZ (yttrium stabilized zirconia).

[0006] In a second aspect, the present invention provides a method for preparing a positive electrode material, comprising the following steps:

[0007] Step 1, mixing a barium source, an iron source, a vanadium source, and a molybdenum source to obtain a mixed powder, pre-sintering the mixed powder in air, heating it, and then roasting it in a reducing atmosphere to obtain a first coating layer material; wherein the molar ratio of barium in the barium source, iron in the iron source, vanadium in the vanadium source, and molybdenum in the molybdenum source is 2:1:x:(1-x), 0.01≤x≤0.1;

[0008] Step 2, ball milling the first coating layer material and the matrix material and then calcining them in an inert atmosphere to obtain an intermediate product; wherein the matrix material is NaNi x1 Fe y1 Mn z1 O2, 0<x1≤0.8, 0<y1≤0.4, 0<z1≤0.4, x1+y1+z1=1;

[0009] Step 3, adding the intermediate product, zirconium source and yttrium source into ethanol and adjusting the pH value of the reaction system to 7-9 for a certain period of time to obtain a slurry, then filtering the slurry, drying the obtained solid particles, and calcining them under an inert atmosphere to obtain the positive electrode material.

[0010] Preferably, in step 1, the pre-firing temperature is 800-950° C., and the pre-firing time is 7-10 h; the roasting temperature is 900-1200° C., and the roasting time is 10-15 h.

[0011] Preferably, the barium source is any one or more of barium oxalate, barium carbonate, barium nitrate, barium sulfate, barium chloride and barium oxide; more preferably, the barium source is barium carbonate.

[0012] Preferably, the iron source is any one or more of ferric oxide, ferric nitrate, ferric acetate, and ferric oxalate; more preferably, the iron source is ferric oxide.

[0013] Preferably, the vanadium source is any one or more of vanadium pentoxide, ammonium metavanadate, vanadium oxyacetate, and vanadium oxalate; more preferably, the vanadium source is vanadium pentoxide.

[0014] Preferably, the molybdenum source is any one or more of ammonium molybdate, molybdenum oxide, and molybdic acid; more preferably, the molybdenum source is molybdenum oxide.

[0015] Preferably, in step 2, the mass of the first coating layer material is 2% to 10% of the mass of the base material.

[0016] Preferably, in step 2, the calcination temperature is 700-900° C., and the calcination time is 8-12 hours.

[0017] Preferably, in step 3, the zirconium source is any one or more of zirconium oxychloride, zirconium oxynitrate and zirconium oxysulfate; more preferably, the zirconium source is zirconium oxychloride.

[0018] Preferably, the yttrium source is yttrium nitrate.

[0019] Preferably, in step 3, the concentration of zirconium in the slurry is 0.02-0.1 mol / L; the concentration of yttrium in the slurry is 0.002-0.01 mol / L.

[0020] Preferably, in step 3, the pH adjuster is aqueous ammonia.

[0021] Preferably, in step 3, the reaction time is 1 to 5 hours.

[0022] Preferably, in step 3, the drying temperature is 70-100° C., and the drying time is 8-15 h; more preferably, the drying temperature is 80-90° C., and the drying time is 10-12 h.

[0023] Preferably, in step 3, the calcination temperature is 600-900° C., and the calcination time is 6-10 h; more preferably, the calcination temperature is 700-800° C., and the calcination time is 7-8 h.

[0024] In a third aspect, the present invention provides a battery, comprising the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned preparation method.

[0025] Compared with the prior art, the present invention has the following obvious beneficial effects:

[0026] The present invention adopts Ba2FeV x Mo 1-x O6 and YSZ are used to coat the base material, Ba2FeV x Mo 1-x O6 material has excellent conductivity and structural stability, Ba2FeV x Mo 1-x O6 coated positive electrode material can improve the stability and conductivity of the positive electrode material in high temperature environment; YSZ (yttrium stabilized zirconia) has good corrosion resistance and ion conductivity. The introduction of YSZ material on the surface of the positive electrode material can not only effectively inhibit the decomposition reaction between the electrolyte and the positive electrode material, but also further improve the long-term performance of the positive electrode material in high temperature environment, so that the battery also has excellent cycle performance, stability and conductivity in high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1 of the present invention;

[0028] Figure 2 The cycle performance test diagram of the battery assembled with the positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 of the present invention;

[0029] Figure 3 The electrochemical impedance spectroscopy (EIS) test diagram of the battery assembled with the positive electrode materials prepared in Example 1 and Comparative Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0030] The present invention provides the following specific technical solutions.

[0031] In a first aspect, the present invention provides a positive electrode material, comprising a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on at least a portion of the surface of the substrate, and the second coating layer is coated on at least a portion of the surface of particles formed by the first coating layer and the substrate; the substrate is NaNi x1 Fe y1 Mn z1 O2, 0<x1≤0.8, 0<y1≤0.4, 0<z1≤0.4, x1+y1+z1=1; the first coating layer is Ba2FeV x Mo 1-x O6, 0.01≤x≤0.1; the second coating layer is YSZ (yttrium stabilized zirconia).

[0032] In the prior art, the stability and electrochemical performance of the positive electrode material of sodium ion batteries deteriorate under high temperature environments, affecting the cycle life and electrochemical performance of the battery. x Mo 1-x O6 has excellent conductivity and stability. Its ordered cation arrangement can provide more flexible ion channels, allowing sodium ions to diffuse faster. Ba2FeV x Mo 1-x The V element in the O6 material can enhance the material's high-temperature oxidation resistance. Coating it on the surface of the positive electrode material can provide better stability and ion conductivity under high temperature conditions, and can avoid the performance degradation of the material due to phase change during long-term high-temperature cycles. Furthermore, the introduction of YSZ (yttrium-stabilized zirconia) on the surface of the positive electrode material can effectively inhibit the decomposition reaction between the electrolyte and the positive electrode material, and can further improve the long-term performance of the positive electrode material in a high-temperature environment. YSZ has good chemical inertness and thermal stability, and can provide excellent interface protection for the positive electrode material under extreme conditions, preventing oxidation and decomposition of the electrode material, thereby improving the long-term performance of the positive electrode material in a high-temperature environment, and enabling the battery to have excellent cycle performance and electrochemical performance in a high-temperature environment. Ba2FeV x Mo 1-x The combination of O6 and YSZ coating can not only make the material have long-term stability in high temperature environment, but also obtain good high-voltage performance and rate performance.

[0033] In a second aspect, the present invention provides a method for preparing a positive electrode material, comprising the following steps:

[0034] Step 1, mixing a barium source, an iron source, a vanadium source, and a molybdenum source to obtain a mixed powder, pre-sintering the mixed powder in air, heating it, and then roasting it in a reducing atmosphere to obtain a first coating layer material; wherein the molar ratio of barium in the barium source, iron in the iron source, vanadium in the vanadium source, and molybdenum in the molybdenum source is 2:1:x:(1-x), 0.01≤x≤0.1;

[0035] Step 2, ball milling the first coating layer material and the matrix material and then calcining them in an inert atmosphere to obtain an intermediate product; wherein the matrix material is NaNi x1 Fe y1 Mn z1 O2, 0<x1≤0.8, 0<y1≤0.4, 0<z1≤0.4, x1+y1+z1=1;

[0036] Step 3, adding the intermediate product, zirconium source and yttrium source into ethanol and adjusting the pH value of the reaction system to 7-9 for a certain period of time to obtain a slurry, then filtering the slurry, drying the obtained solid particles, and calcining them under an inert atmosphere to obtain the positive electrode material.

[0037] In the actual production process, the mixed powder is first pre-sintered in an air atmosphere to completely decompose the carbonate in the raw materials and make the raw materials react initially. Then the temperature is raised and sintered in a reducing atmosphere to obtain Ba2FeV x Mo 1-x O6 material has good high temperature oxidation resistance, in which Fe ions and Mo ions are 3+ / Fe 2+ and Mo 6+ / Mo 5+ The yttrium ions in the prepared YSZ replace some zirconium sites in the zirconium oxide lattice to form a stable cubic phase or tetragonal phase. The first coating layer, the second coating layer and the matrix material cooperate with each other to improve the electrochemical performance and cycle performance of the positive electrode material.

[0038] In step 1, the gas providing the reducing atmosphere is usually H2.

[0039] Preferably, in step 1, the pre-firing temperature is 800-950° C., and the pre-firing time is 7-10 h; the roasting temperature is 900-1200° C., and the roasting time is 10-15 h.

[0040] The calcination temperature is higher than the pre-calcination temperature. Pre-calcination can remove volatile and decomposable impurities such as moisture, make the mixed material react initially to form an intermediate phase or precursor phase, and remove gas to reduce the volume change in the subsequent sintering process, thereby avoiding defects such as cracks. It is conducive to the subsequent calcination to form the target phase. The combination of pre-calcination and calcination can make the material crystal form better, regulate the microstructure of the material, make the grains of the target product uniform, and reduce organizational defects.

[0041] Furthermore, if the pre-firing temperature is too low, the organic matter and volatile impurities in the raw materials may not be completely removed, the intermediate phase may not be formed, and the impurity phase is easy to be generated, which may lead to reduced purity of the generated material and incomplete crystal structure during the subsequent calcination process. If the pre-firing temperature is too high, it is easy to cause agglomeration, which is not conducive to the complete transformation of the phase. If the calcination temperature is too low, the reaction is insufficient, and the precursor phase cannot be completely transformed into the target phase, resulting in residual impurities in the material, thereby affecting the purity and performance of the target product, and easily leading to incomplete grain development and more internal defects in the crystal. If the calcination temperature is too high, it is easy to cause excessive grain growth and sintering, and the grain size is too large, thereby reducing the specific surface area and reaction activity of the material, which is not conducive to practical application. High temperature may also cause phase change of the material, resulting in instability of the crystal structure and the formation of other impurities.

[0042] Preferably, the barium source is any one or more of barium oxalate, barium carbonate, barium nitrate, barium sulfate, barium chloride and barium oxide; more preferably, the barium source is barium carbonate.

[0043] Preferably, the iron source is any one or more of ferric oxide, ferric nitrate, ferric acetate, and ferric oxalate; more preferably, the iron source is ferric oxide.

[0044] Preferably, the vanadium source is any one or more of vanadium pentoxide, ammonium metavanadate, vanadium oxyacetate, and vanadium oxalate; more preferably, the vanadium source is vanadium pentoxide.

[0045] Preferably, the molybdenum source is any one or more of ammonium molybdate, molybdenum oxide, and molybdic acid; more preferably, the molybdenum source is molybdenum oxide.

[0046] Preferably, in step 2, the mass of the first coating layer material is 2% to 10% of the mass of the base material.

[0047] The inventors have found that if the coating is too thick, the diffusion path of ions and electrons will be too long, increasing the charge transfer impedance; the coating layer and the positive electrode material may be separated or cracked, affecting stability; and the material cost will increase. If the coating is too thin, the surface of the positive electrode material cannot be fully covered, affecting the synergistic effect of the coating material and the base material; and the uniformity of the thin layer coating may be poor, affecting the performance of the material.

[0048] Preferably, in step 2, the calcination temperature is 700-900° C., and the calcination time is 8-12 hours.

[0049] The inventors have found that if the calcination temperature is too high, the elements in the base material may diffuse or form new phases, destroying the material structure, and may also cause the base positive electrode material to overburn and destroy the structure; if the temperature is too low, it is not enough to fully combine the coating layer with the surface of the positive electrode material, resulting in weak adhesion of the coating layer. The coating layer is not firmly bonded to the positive electrode material and is prone to fall off or cracks during the charge and discharge process.

[0050] Preferably, the zirconium source is any one or more of zirconium oxychloride (ZrOCl2), zirconium oxynitrate (ZrO(NO3)2), and zirconium oxysulfate (ZrOSO4); more preferably, the zirconium source is zirconium oxychloride (ZrOCl2).

[0051] Preferably, the yttrium source is yttrium nitrate (Y(NO3)3).

[0052] Preferably, in step 3, the concentration of zirconium in the slurry is 0.02-0.1 mol / L; the concentration of yttrium in the slurry is 0.002-0.01 mol / L.

[0053] The concentration of zirconium and yttrium in the slurry affects the coating thickness. If the concentration is too high, the coating may be too thick, resulting in too long diffusion paths for ions and electrons, increased charge transfer impedance, possible detachment or cracks between the coating and the positive electrode material, and increased stability. Material costs will increase. If the concentration is too low, the coating may be too thin and unable to fully cover the surface of the positive electrode material, thus failing to function effectively, and the uniformity of the thin layer coating may be poor.

[0054] Preferably, in step 3, the pH adjuster is aqueous ammonia.

[0055] Preferably, in step 3, the reaction time is 1 to 5 hours.

[0056] Preferably, in step 3, the drying temperature is 70-100° C., and the drying time is 8-15 h; more preferably, the drying temperature is 80-90° C., and the drying time is 10-12 h.

[0057] Preferably, in step 3, the calcination temperature is 600-900° C., and the calcination time is 6-10 h; more preferably, the calcination temperature is 700-800° C., and the calcination time is 7-8 h.

[0058] In a third aspect, the present invention provides a battery, comprising the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned preparation method.

[0059] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0060] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0061] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0062] Embodiment 1:

[0063] A method for preparing a positive electrode material comprises the following steps:

[0064] Step 1, mixing barium carbonate, ferric oxide, vanadium pentoxide and molybdenum oxide to obtain a mixed powder, wherein the molar ratio of barium in the barium carbonate, iron in the ferric oxide, vanadium in the vanadium pentoxide and molybdenum in the molybdenum oxide is 2:1:0.05:0.95.

[0065] Step 2: pre-sinter the mixed powder at 900° C. for 9 hours in an air atmosphere, and grind the solid particles obtained after pre-sintering.

[0066] Step 3: transfer the solid particles obtained in step 2 to a tube furnace, calcine at 1000°C for 12 h in a hydrogen atmosphere, and cool to room temperature to obtain Ba2FeV 0.05 Mo 0.95 O6 material.

[0067] Step 4: Mix 0.5 g of Ba2FeV 0.05 Mo 0.95 O6 material and 10g of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The O2 material is ball-milled, and then the solid particles after ball milling are transferred to a muffle furnace and calcined at 800 °C for 10 h under an inert atmosphere to obtain an intermediate product.

[0068] Step 5, dissolve 1.1562g of zirconium oxynitrate and 0.1375g of yttrium nitrate in 100ml of ethanol, stir until dissolved, add 10g of the intermediate product obtained in step 4, add ammonia water to adjust the pH to 7.5, stir until no more precipitation occurs and then let stand for 2h; filter to obtain solid particles, dry the obtained solid particles at 80°C for 12h, then heat to 700°C and calcine for 8h to obtain the positive electrode material.

[0069] Figure 1is a SEM image of the positive electrode material obtained in Example 1. Figure 1 It can be seen that the primary particles of the prepared positive electrode material are flake-shaped and spherical as a whole. The coating layer is tightly coated on the surface of the material without agglomeration.

[0070] Comparative Example 1:

[0071] The difference from Example 1 is that the positive electrode material is not coated, and the positive electrode material is NaNi 1 / 3 Fe 1 / 3Mn 1 / 3 O2.

[0072] Comparative Example 2:

[0073] The difference from Example 1 is that the intermediate product obtained in step 4 is the target positive electrode material, and the positive electrode material is Ba2FeV 0.05 Mo 0.95 O6 material coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0074] Comparative Example 3:

[0075] A method for preparing a positive electrode material comprises the following steps:

[0076] Step 1: Dissolve 1.1562g zirconium oxynitrate and 0.1375g yttrium nitrate in 100ml ethanol, stir until dissolved, and add 10g NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, adjust the pH to 7.5, stir continuously, filter to obtain solid particles, dry the obtained solid particles at 80°C for 12h, then heat to 700°C and calcine for 8h to obtain the positive electrode material.

[0077] Embodiment 2:

[0078] A method for preparing a positive electrode material comprises the following steps:

[0079] Step 1, mixing barium oxalate, iron oxalate, vanadium oxalate and ammonium molybdate to obtain a mixed powder, wherein the molar ratio of barium in barium oxalate, iron in iron oxalate, vanadium in vanadium oxalate and molybdenum in ammonium molybdate is 2:1:0.01:0.99.

[0080] Step 2: pre-sinter the mixed powder at 800° C. for 8 h in an air atmosphere, and grind the solid particles obtained after pre-sintering.

[0081] Step 3: transfer the solid particles obtained in step 2 to a tube furnace, calcine at 1100°C for 10 h in a hydrogen atmosphere, and cool to room temperature to obtain Ba2FeV 0.01Mo 0.99 O6 material.

[0082] Step 4: Mix 0.2g of Ba2FeV 0.01 Mo 0.99 O6 material and 10g of NaNi 0.2 Fe 0.4 Mn 0.4 The O2 material is ball-milled, and then the solid particles after ball milling are transferred to a muffle furnace and calcined at 700 °C for 8 h under an inert atmosphere to obtain an intermediate product.

[0083] Step 5, dissolve 0.4625g of zirconium oxynitrate and 0.0550g of yttrium nitrate in 100ml of ethanol, stir until dissolved, add 10g of NaNi0.2Fe0.4Mn0.4O2, adjust the pH to 7, stir until no more precipitate is precipitated, let stand for 1h, filter to obtain solid particles, dry the obtained solid particles at 70°C for 8h, then heat to 600°C and roast for 6h to obtain the positive electrode material.

[0084] Embodiment 3:

[0085] A method for preparing a positive electrode material comprises the following steps:

[0086] Step 1, mixing barium nitrate, ferric nitrate, vanadium acetate and ammonium molybdate to obtain a mixed powder, wherein the molar ratio of barium in the barium nitrate, iron in the ferric nitrate, vanadium in the vanadium acetate and molybdenum in the ammonium molybdate is 2:1:0.1:0.90.

[0087] Step 2: pre-sinter the mixed powder at 950° C. for 10 h in an air atmosphere, and grind the solid particles obtained after pre-sintering.

[0088] Step 3: transfer the solid particles obtained in step 2 to a tube furnace, calcine at 1200°C for 15 h in a hydrogen atmosphere, and cool to room temperature to obtain Ba2FeV 0.1 Mo 0.9 O6 material.

[0089] Step 4: Mix 1g of Ba2FeV 0.1 Mo 0.9 O6 material and 10g of NaNi 0.4 Fe 0.2 Mn 0.4 O2 material and ball milled, and then the ball-milled solid particles were transferred to a muffle furnace and calcined at 900 ° C for 12 h under an inert atmosphere to obtain an intermediate product.

[0090] Step 5: Add 2.3123 g zirconium oxynitrate and 0.2749 g yttrium nitrate to 100 ml ethanol, stir until dissolved, and add 10 g NaNi 0.4 Fe 0.2M n0.4 O2, adjust the pH to 9, stir until no more precipitation occurs, then let stand for 3 hours, filter to obtain solid particles, dry the obtained solid particles at 100°C for 15 hours, and then heat to 900°C and calcine for 10 hours to obtain the positive electrode material.

[0091] The positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were assembled into a battery. The positive electrode material: conductive graphite: PVDF mass ratio was 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) was added and continued to grind and stir to form a uniform slurry. The slurry was evenly coated on an aluminum foil with a mold, and the coating thickness was 200 μm. The aluminum foil was placed in a drying oven at 90°C for 10 hours, and then cut into discs with a diameter of 12 mm. The disc was used as the positive electrode, the sodium sheet was used as the negative electrode, and 1 mol / L NaPF6 / EC+DEC+DMC was used as the electrolyte. The battery was assembled in a glove box in the order of button-type battery assembly.

[0092] The performance test of the assembled battery was carried out. The assembled battery, which had been left to stand overnight, was placed in a LAND2001CT battery test box for charge and discharge test. The test was carried out at 60°C and a cycle voltage of 2-4V for 50 cycles. Figure 2 This is a test chart of the cycle performance of batteries assembled from the positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3.

[0093] Depend on Figure 2 It can be seen that the overall trend of the battery assembled with the positive electrode material prepared by the present invention after 50 cycles at 60°C is more gentle, indicating that the positive electrode material prepared by the present invention has better cycle stability, and the test at a high temperature of 60°C shows that the positive electrode material provided by the present invention has good high temperature stability.

[0094] Depend on Figure 2 It can be observed that the initial capacity of Example 2 is relatively low. The inventors analyzed the reason as follows: the matrix material used in Example 2 is NaNi 0.2 Fe 0.4 Mn 0.4 O2, with lower nickel content, results in lower initial capacity.

[0095] The battery assembled with the positive electrode materials obtained in Example 1 and Comparative Examples 1 to 3 was subjected to electrochemical impedance spectroscopy (EIS) test. At 25°C, the voltage was set to 4V, the scanning frequency was 1mHz to 100kHz, and data of 12 points were collected in each 10-fold frequency interval. The AC signal amplitude at each frequency point was 10mV. The test data is shown in FIG. Figure 3 .

[0096] Depend on Figure 3 It can be seen that Ba2FeV 0.05 Mo 0.95The battery impedance of Example 1 with O6 and YSZ synergistic coating is the smallest, indicating that Ba2FeV 0.05 Mo 0.95 The synergistic coating of O6 and YSZ can improve the rapidity of the material's charge transfer process and has good reaction kinetics, which also means that the positive electrode material has good ionic conductivity.

[0097] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The invention comprises a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on at least a part of the surface of the substrate, and the second coating layer is coated on at least a part of the surface of the particles formed by the first coating layer and the substrate; the substrate is NaNi x1 Fe y1 Mn z1 O2, 0<x1≤0.8, 0<y1≤0.4, 0<z1≤0.4, x1+y1+z1=1; the first coating layer is Ba2FeV x Mo 1-x O6, 0.01≤x≤0.1; the second coating layer is YSZ (yttrium stabilized zirconia).

2. A method for preparing a positive electrode material, characterized in that: The steps include: Step 1, mixing a barium source, an iron source, a vanadium source, and a molybdenum source to obtain a mixed powder, pre-sintering the mixed powder in air, heating it, and then roasting it in a reducing atmosphere to obtain a first coating layer material; wherein the molar ratio of barium in the barium source, iron in the iron source, vanadium in the vanadium source, and molybdenum in the molybdenum source is 2:1:x:(1-x), 0.01≤x≤0.1; Step 2, ball milling the first coating layer material and the matrix material and then calcining them in an inert atmosphere to obtain an intermediate product; wherein the matrix material is NaNi x1 Fe y1 Mn z1 O2, 0<x1≤0.8, 0<y1≤0.4, 0<z1≤0.4, x1+y1+z1=1; Step 3, adding the intermediate product, zirconium source and yttrium source into ethanol and adjusting the pH value of the reaction system to 7-9 for a certain period of time to obtain a slurry, then filtering the slurry, drying the obtained solid particles, and calcining them under an inert atmosphere to obtain the positive electrode material; In step 1, the pre-firing temperature is 800-950°C, and the pre-firing time is 7-10 hours; the roasting temperature is 900-1200°C, and the roasting time is 10-15 hours; In step 2, the calcination temperature is 700-900° C., and the calcination time is 8-12 hours.

3. The method for preparing the positive electrode material according to claim 2, characterized in that: The barium source is any one or more of barium oxalate, barium carbonate, barium nitrate, barium sulfate, barium chloride, and barium oxide; the iron source is any one or more of ferric oxide, ferric nitrate, ferric acetate, and ferric oxalate; the vanadium source is any one or more of vanadium pentoxide, ammonium metavanadate, vanadium acetate, and vanadium oxalate; the molybdenum source is any one or more of ammonium molybdate, molybdenum oxide, and molybdic acid; the zirconium source is any one or more of zirconium oxychloride, zirconium oxynitrate, and zirconium oxy sulfate; and the yttrium source is yttrium nitrate.

4. The method for preparing the positive electrode material according to claim 2, characterized in that: In step 2, the mass of the first coating layer material is 2% to 10% of the mass of the base material.

5. The method for preparing the positive electrode material according to claim 2, characterized in that: In step 3, the concentration of zirconium in the slurry is 0.02-0.1 mol / L; the concentration of yttrium in the slurry is 0.002-0.01 mol / L.

6. The method for preparing the positive electrode material according to claim 2, characterized in that: In step 3, the drying temperature is 70-100° C., and the drying time is 8-15 hours; the roasting temperature is 600-900° C., and the roasting time is 6-10 hours.

7. The method for preparing the positive electrode material according to claim 2, characterized in that: In step 3, the reaction time is 1 to 5 hours.

8. A battery, characterized in that: Including the positive electrode material according to claim 1 or the positive electrode material prepared by the preparation method according to any one of claims 2 to 7.

Citation Information

Patent Citations

  • Sodium ion positive electrode material and preparation method and application thereof

    CN115000388A

  • Modified LNCM712 ternary positive electrode material and preparation method thereof

    CN116314744A